Can the workload-injury relationship be moderated by improved strength, speed and repeated-sprint qualities? - Malone, S.; Hughes, B.; Doran, D. A.; Collins, K.; Gabbett, T. J. (Journal of Science and Medicine in Sport, 2019)
Objectives: The aim of this study was to investigate potential moderators (i.e. lower body strength, repeated-sprint ability [RSA] and maximal velocity) of injury risk within a team-sport cohort. Design: Observational cohort study. Methods: Forty male amateur hurling players (age: 26.2 ± 4.4 year, height: 184.2 ± 7.1 cm, mass: 82.6 ± 4.7 kg) were recruited. During a two-year period, workload (session RPE × duration), injury and physical qualities were assessed. Specific physical qualities assessed were a three-repetition maximum Trapbar deadlift, 6 × 35-m repeated-sprint (RSA) and 5-, 10- and 20-m sprint time. All derived workload and physical quality measures were modelled against injury data using regression analysis. Odds ratios (OR) were reported against a reference group. Results: Moderate weekly loads between =1400 AU and =1900 AU were protective against injury during both the pre-season (OR: 0.44, 95% CI: 0.18-0.66) and in-season periods (OR: 0.59, 95% CI: 0.37-0.82) compared to a low load reference group (=1200 AU). When strength was considered as a moderator of injury risk, stronger athletes were better able to tolerate the given workload at a reduced risk. Stronger athletes were also better able to tolerate larger week-to-week changes (>550-1000 AU) in workload than weaker athletes (OR = 2.54-4.52). Athletes who were slower over 5-m (OR: 3.11, 95% CI: 2.33-3.87), 10-m (OR: 3.45, 95% CI: 2.11-4.13) and 20-m (OR: 3.12, 95% CI: 2.11-4.13) were at increased risk of injury compared to faster athletes. When repeated-sprint total time (RSAt) was considered as a moderator of injury risk at a given workload (=1750 AU), athletes with better RSAt were at reduced risk compared to those with poor RSAt (OR: 5.55, 95%: 3.98-7.94). Conclusions: These findings demonstrate that well-developed lower-body strength, RSA and speed are associated with better tolerance to higher workloads and reduced risk of injury in team-sport athletes. ABSTRACT FROM AUTHOR